Impact of the top-down quota-oriented farmland preservation planning on the change of urban land-use intensity in China. (July 2018) - Zhong, Taiyang; Qian, Zhu; Huang, Xianjin; Zhao, Yuntai; Zhou, Yan; Zhao, Zehui
Abstract: Although the National General Land Use Plan (1997–2010) came into effect in 1999, there has been no research investigating whether the farmland protection planning embedded within the top-down general land-use plans has contributed to promoting intensive utilization of urban land. This paper aims to assess the impact of farmland preservation efforts in the plans on the changes in urban land-use intensity, by focusing on two policy tools – prime farmland preservation and farmland conversion quotas. The study developed an approach to categorize and measure the change in urban land-use intensity by combining the changes in population density (in terms of population per unit of urban land area) and economic density (in terms of GDP per unit of urban land area). An ordinal dependent variable was generated based on the categories of changes in urban land-use intensity and a multilevel ordinal logit model was used in this study. The study indicates that (1) the farmland conversion quota system did not contribute to promoting urban land-use intensification between 2000 and 2010; (2) the prime farmland preservation had very limited impact on the intensity of urban land-use intensification. The prime farmland preservation would not influence urban land-use intensity when it was not high enough. The increase in the prime farmland preservation ratio in prefectural-level regions could lead to urban land-use intensification but only when the prime farmland preservation ratio was above 93%; and (3) the central government's supervision of local land-use played a significant role in promoting urban land-use intensification.